The ascidian Asterocarpa humilis (Heller, 1878) in the South Western Atlantic: A native or introduced species? - Taverna, Anabela Jesús (2018)
Taxonomic problems when dealing with morphologically similar marine taxa can hinder the correct assignment of the status of a species as native or introduced. This is the case of Asterocarpa humilis (Heller, 1878) considered native for the Southern Hemisphere. The species was originally described for New Zealand and later cited for Tasmania and South Africa. However, for Chile A. humilis was considered introduced, as well as for the Northern Hemisphere in Great Britain and France. For the SW Atlantic, another species with a similar morphology, Cnemidocarpa robinsoni Hartmeyer, 1918 has been reported as a cryptogenic species. The aim of this work was to define the entity and status of these species: Asterocarpa humilis and Cnemidocarpa robinsoni through molecular analyses. We sequenced a partial fragment of COI gene of seven samples of C. robinsoni collected at the Argentine Sea. A median joining haplotype network was constructed including the seven new sequences and four sequences of A. humilis from Chile, New Zealand and France mined from published databases. Four haplotypes with eight variable sites were obtained. The haplotype network shows a more frequent haplotype present in South America and France, suggesting that the Argentine specimens described as C. robinsoni and those from Chile and France as A. humilis, correspond to the same taxonomic entity. Phylogenetic trees reconstructed by Bayesian Inference, Maximum Likelihood and Maximum Parsimony, grouped A. humilis and C. robinsoni into one well-supported monophyletic clade. The scarce genetic difference among individuals from distant populations proves the existence of a unique specific identity. Thus, the name Asterocarpa humilis takes precedence over Cnemidocarpa robinsoni; the latter must be considered a junior synonym of the former. The presence of this species in natural habitats in addition to its register in old collections (1920) in the SW Atlantic, suggests that the species is native for this area.